2014
DOI: 10.1016/j.addr.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels to model 3D in vitro microenvironment of tumor vascularization

Abstract: A growing number of failing clinical trials for cancer therapy is substantiating the need to upgrade the current practice in culturing tumor cells and modeling tumor angiogenesis in vitro. Many attempts have been made to engineer vasculature in vitro by utilizing hydrogels, but the application of these tools in simulating in vivo tumor angiogenesis is still very new. In this review, we explore current use of hydrogels and their design parameters to engineer vasculogenesis and angiogenesis and to evaluate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 140 publications
(174 reference statements)
0
116
0
2
Order By: Relevance
“…Conventional two-dimensional (2D) monolayer models of human cancers have been important tools for studying cancer biology and developing anticancer therapeutics, and provide a valuable addition to what can be learned using animal models. However, it is becoming increasingly clear that conventional 2D culture models are insufficient to recapitulate many important characteristics of tumors in vivo and are often poorly predictive of drug response in humans 2931 . In contrast to 2D monolayer culture models, tumor cells in vivo are supported by a 3D extracellular matrix (ECM) and non-tumor cells, including endothelial cells, immune cells, and other stromal cells 1,32 .…”
Section: Biomaterials To Create 3d Tumor Modelsmentioning
confidence: 99%
“…Conventional two-dimensional (2D) monolayer models of human cancers have been important tools for studying cancer biology and developing anticancer therapeutics, and provide a valuable addition to what can be learned using animal models. However, it is becoming increasingly clear that conventional 2D culture models are insufficient to recapitulate many important characteristics of tumors in vivo and are often poorly predictive of drug response in humans 2931 . In contrast to 2D monolayer culture models, tumor cells in vivo are supported by a 3D extracellular matrix (ECM) and non-tumor cells, including endothelial cells, immune cells, and other stromal cells 1,32 .…”
Section: Biomaterials To Create 3d Tumor Modelsmentioning
confidence: 99%
“…Transwell ®), as well as immunofluorescent or immunohistochemical staining and imaging [4,19,20]. However, the inability of 2D culture to accurately predict therapeutic response and the complexity of animal models has paved the way for the development of 3D in vitro models, which utilize materials such as hydrogels to recapitulate elements of the tumor microenvironment [21][22][23]. To date, 3D in vitro models for GBM primarily incorporate only tumor cells, despite the demonstrated contributions of additional cell types to in vivo GBM behavior [6,[24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…One particular approach to create in vitro models of blood vessels is worth mentioning for microbubble-related medical applications, since it consists of embedding a functional vascular network in a hydrogel ECM-like matrix, which can act as the surrounding tissue. 63 This approach would allow not only the study of the microbubble delivery under physiological flow conditions followed by the rupture of the barrier upon bubble excitation, but also the visualization of the actual release of drugs and the assessment of its penetration into the tissue. Moya et al 64 reported the spontaneous formation of such a complex vasculature in a fibrin matrix.…”
Section: More Complex Cellular Models: Toward Mimicking the In Vivmentioning
confidence: 99%